Complementary Schottky diode formation with carbon buffer and p-doped single layer graphene on intrinsic SiC via fluorine intercalation. (February 2019) - Lee, Sang Yeon; Kim, Jinseo; Ahn, Seungbae; Jeon, Ki-Joon; Seo, Hyungtak
Abstract: A practical application of graphene is in transistors and diodes fabricated through processes compatible with integrated circuit fabrication processes that are currently used. In this paper, a highly controlled gas phase fluorination treatment (using XeF2 ) of an intrinsic Si-terminated SiC (i-SiC) substrate and a (6√3ⅹ6√3)R30° carbon buffer layer is shown to effectively convert the buffer layer to p- doped SLG ( p- SLG), which is decoupled from the i-SiC substrate through F intercalation. The electrical properties of two diode structures, (1) metal/SiC with buffer layer and (2) p- SLG/SiC, were investigated considering the bias-dependent carrier injection at each interface. The analysis results suggest that the diode turn-on for each diode is due to carrier injection from the metal or p- SLG to the i-SiC substrate, with an exponential modulation of the thermionic injection driven by the image barrier lowering effect. A complementary SLG-based SiC diode formation scheme is demonstrated, as hole injection from p- SLG is the origin of positive bias diode turn-on in the second diode type, whereas the diode having metal/SiC with buffer structure showed negative bias turn-on. Graphical abstract: Image 1